Body movements as pain indicators in older people with cognitive impairment: A systematic review. (10th December 2018) - Strand, Liv Inger; Gundrosen, Kim Fredrik; Lein, Regina Küfner; Laekeman, Marjan; Lobbezoo, Frank; Defrin, Ruth; Husebo, Bettina S.
Abstract: Background and objective: Pain assessment tools for cognitively impaired older people, unable to self‐report pain, are commonly founded upon observation of pain behaviour, such as facial expressions, vocalizations and body movements. The scientific basis for claiming that body movements may indicate pain has not formerly been investigated in a systematic review. The objective was to explore research evidence for body movements being pain indicators in older people with cognitive impairment. Data bases and data treatment: MEDLINE, EMBASE, CINAHL, PsycINFO and the Cochrane Library were searched systematically. Two researchers independently identified and consented on studies to be included. PRISMA statement for reporting systematic reviews was followed. Mixed Methods Appraisal Tool was used for critical evaluation of study quality. Results: A total of 2, 096 records from the literature searches were identified, and 17 quantitative and eight qualitative studies were included in the review, the studies mainly related to older people with dementia. Quality scores ranged from 50% to 100%. We combined 62 items of body movements into 13 similar or synonymous items, and criteria for evidence were defined. Strong evidence was found for restlessness (agitation), rubbing, guarding, rigidity and physical aggression as the behaviours frequently responded (increased or decreased) to pain provoking activities, painful procedures and/or pain medication. Conclusions: Among 13 categories of body movements, we found five with strong and five with moderate evidence of validity. As few items were typically included in many studies reflecting criterion validity, all should be included in future studies of patients with different characteristics, location and duration of pain. Significance: Pain assessment tools for older people with cognitive impairment or dementia should include valid pain behaviour items. Our review shows strong scientific evidence for the following body movements indicating pain: restlessness (agitation), rubbing, guarding, rigidity and physical aggression .